Efficient Peroxydisulfate Activation Process Not Relying on Sulfate Radical Generation for Water Pollutant Degradation - Zhang, Tao; Chen, Yin; Wang, Yuru; Le Roux, Julien; Yang, Yang; Croué, Jean-Philippe (Environmental science & technology, 2014)
Peroxydisulfate (PDS) is an appealing oxidant for contaminated groundwater and toxic industrial wastewaters. Activation of PDS is necessary for application because of its low reactivity. Present activation processes always generate sulfate radicals as actual oxidants which unselectively oxidize organics and halide anions reducing oxidation capacity of PDS and producing toxic halogenated products. Here we report that copper oxide (CuO) can efficiently activate PDS under mild conditions without producing sulfate radicals. The PDS/CuO coupled process is most efficient at neutral pH for decomposing a model compound, 2,4-dichlorophenol (2,4-DCP). In a continuous-flow reaction with an empty-bed contact time of 0.55 min, over 90% of 2,4-DCP (initially 20 μM) and 90% of adsorbable organic chlorine (AOCl) can be removed at the PDS/2,4-DCP molar ratio of 1 and 4, respectively. Based on kinetic study and surface characterization, PDS is proposed to be first activated by CuO through outer-sphere interaction, the rate-limiting step, followed by a rapid reaction with 2,4-DCP present in the solution. In the presence of ubiquitous chloride ions in groundwater/industrial wastewater, the PDS/CuO oxidation shows significant advantages over sulfate radical oxidation by achieving much higher 2,4-DCP degradation capacity and avoiding the formation of highly chlorinated degradation products. This work provides a new way of PDS activation for contaminant removal.